SOCIAL PARTNERSHIP OF CIVIL SOCIETY ORGANIZATIONS IN THE CONTEXT OF SOCIAL CHANGE - Okushko, Tetiana (Theoretical and Methodical Problems of Children and Youth Education, 2021)
The article highlights the issue of social partnership relevant to pedagogical science and practice. In recent decades, the partnership has been actively involved in various spheres of life of modern societies. In particular, the ideas of social partnership have been widely used in education, civil society organizations. The key concepts of “civil society”, “social partnership of civil society organizations” were defined based on the analysis of scientific sources, modern concepts, generalization and systematization of empirical data on the research topic and social practice. Several normative and legal documents regulating the issues of social partnership in Ukraine have been identified. The experience of realization of social partnership of civil society institutions in Ukraine is described. The author's position on the markers of successful social partnership of civil society institutions is substantiated. The range of existing problems and ways for further scientific research regarding these issues are outlined. In order to achieve the goals and objectives of the study, methods of theoretical search, empirical and statistical analysis were used to summarize the data and results. The practical significance of the study is that its materials could be used in institutions of general secondary, extracurricular and higher education, in departments on affairs of the work with youth of state administrations and united territorial communities, public associations, social services for children and youth.